BAR CODE MEDICATION ADMINISTRATION: A STRATEGIC TECHNOLOGY INTERVENTION FOR REDUCING HOSPITAL’S MEDICATION ERRORS - Elly Wardani (Fakultas Keperawatan-Universitas Syiah Kuala, 2016)
ABSTRACTThe purpose of this review is to investigate the bar code medication administration (BCMA) as a technological solution to reduce preventable medication administration errors. The evidence gathered will serve as a foundation for the hospital board’s executive decision making about the adoption of a technology-based error reduction strategy. The future hope of the implementation of BCMA would be a system that interfaces with other IT (Information Technology) applications to enhance patient safety and quality of care at hospitals. The IT devices, cannot replace caregivers. Yet, the systems would improve and support caregivers’ performance in meeting safety needs and delivering best practices. Keywords: Bar code, medication errors, patient safety.